PENGUKURAN KEPUASAN PELANGGAN MENGGUNAKAN METODE KANO DAN ROOT CAUSE ANALYSIS (STUDI KASUS PLN TANGERANG) - Tiena Gustina Amran; Ponti Ekadeputra (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
National Electric Power Company (Perusahaan Listrik Negara/PLN) according to its commitment has to upgrade its service quality to the society as the only company supplying electrical power where the custoner satisfaction is become a very important matter. By maintaining the customer satisfaction means to upgrade good image of the company and minimizing customer complains. By using the Kano approach which is known as attributes that entered the four areas which are: ‘Must be’, “One dimensional”,”Attractive” and ”Indifferent”. Based on the research carried out it was hoped with the customer's Satisfaction Index in the position which is quite satisfactory. To explore the improvement of problem solution could be done by using Root Cause Analysis which will give big impact to the company. This improvement will appear in the fact of fast services for instance in direct ticket purchasing, installation direct improvemen, and quick respons and contact of the PLN call center.